Խորան բառի ծագումնաբանական ասպեկտները Եվսեբիոսի համաձայնության աղյուսակների գեղարվեստական հարդարանքի համատեքստում - Ռուզաննա Ամիրխանյան (ՀՀ ԳԱԱ հրատ.)
В статье рассматриваются вопросы этимологии армянского термина хоран,с древних пор ассоциирующегося с архитектурными украшениями Таблиц Согласия, предваряющих в средневековых армянских рукописях текст Евангелий. Обсуждаются особенности смыслового употребления термина в разные периоды развития средневековой армянской литературы.The article is dedicated to the etymological analysis of the Armenian term xoran which is associated with artistic decoration of Canon Tables preceding the text of the Gospels in medieval manuscript books. Peculiarities of its use in different ages of medieval Armenian literature are examined, drawing parallels with the iconographic development of Canon Tables' artistic decoration.
Keywords: B Philosophy; Psychology; Religion; Philology; Linguistics; Language and Literature; BL Religion; N Fine Arts; NA Architecture